HAMBATAN PENGGUNAAN DANA SISA LEBIH PERHITUNGAN ANGGARAN STUDI KASUS DI PUSKESMAS KOTA SEMARANG - Dyah Ayu Oktavia; Sutopo Patria Jati; Rani Tiyas Budiyanti (Jurnal Kesehatan Masyarakat (Undip), 2020)
Planning and organizing adequate health financing (health care financing) will help government in a country in order tomobilize, allocate as well use financing overall health efficient and effective. Since implemented Guarantee program Health National start January 2014 still there inner obstaclefund management so every year happened SiLPA. This is because the funds available at the Puskesmas are not only sourced from the National Health Insurance fund but there is also a General Allocation Fund (DAU) and Health Operational Assistance funds (BOK). Based on recapitulation of revenue and expenditure in Semarang City BLUD in 2016, 2017 and 2018 health centers with the highest nominal SiLPA trend, the Tlogosari Wetan health center with SiLPA in 2016 584,718,077, in 2017 822,602,077 and in 2018  822,595. 363.Qualitative research with descriptive approach using indepth interview. Variable Use of Puskesmas SiLPA Funds in Semarang CityMany of the obstacles faced by Puskesmas in the use of SiLPA funds are in allocating the use of large SiLPA funds, when planning to use SiLPA. The large amount of SiLPA makes it difficult to plan budget changes. The Puskesmas does not know about SOP regarding the use of SiLPA contained in Permenkes Number 21 of 2016 and there is no SOP for the use of SiLPA in Semarang City.Puskesmas collect data on Puskesmas needs included in the budget change plan, design a budget change plan throughout the year, use SiLPA funds in accordance with Permenkes number 21 2016, before the Public Health office an SOP on the use of SiLPA funds for Semarang City.